Digital Vietnam : The Path to Tomorrow - World Bank (World Bank, Washington, DC, 2021)
The report reviews the recent developments in the Vietnamese economy and discusses the economy’s short- to medium-term prospects, highlighting domestic and external risks associated to the COVID-19 (coronavirus) pandemic. A special emphasis is on what Vietnam needs to do to realize its objective of becoming one of the most advanced digital economies in the world while maximizing the benefits from this transformation.